The acceptability of four dimension (4D) virtual construction in Malaysia - Ali, Maisarah; Mohd Noor , Julia (2011)
The problem of delay in construction industry is a global phenomenon and the construction industry in Malaysia is no exception. In the current day context, despite significant benefits in terms of time and cost savings gained through the systematic use of 4D technologies on construction projects, Malaysia construction industry has yet to embrace this 4D CAD technology. The objective of the study find out the acceptability of 4D planning tool as a to tool to mitigate delays during project control among construction practitioners focusing on the construction phase of project life cycle. Surveys and semi-structured interviews were accomplished on 169 respondents comprising of the clients, local authorities or regulatory bodies, contractors and consultants. The responses obtained indicates that 96.3% acknowledges the application of this new 4D technology as a useful tool with good potential to mitigate delays in relation to visualization, analysis and communication. Based on the outcome of the study, it is recommended that financial and technical support be made available before its actual implementation can be realized. Keywords Malaysian construction industry, 4D, visualization, communication, mitigate delay